Theoretical Investigations of High Power Yb3+: YAG Thin-Disk Laser - Mohammed, mustafa; Shihab Ahmed, Mudhir (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
The present study includes a theoretical treatment to derive the general equations of pumping threshold power ( ), laser output power (Pout), and laser device efficiency (ƞ) of the element-doped thin-disk laser (Yb3+) with a quasi-three-level pumping scheme in the continuous wave mode at a temperature of (299K°). In this study, the host crystals (YAG) were selected as typical examples of this laser design in a Gaussian transverse mode. The numerical solution of these equations was made using Matlab software by selecting the basic parameters from the recently published scientific articles for the laser design of these crystal hosts. According to this simulation, this article studied the effect of concentration (N), pumping spot radius (rp), the number of times the pumping beam passes over the disk (Mp), and the pumping power on the laser output power.